Spatial–Temporal Dynamics of Land Use and Cover in Mata da Pimenteira State Park Based on MapBiomas Brasil Data: Perspectives and Social Impacts - Cruz, Júlio Cesar Gomes da; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Silva, Anderson Santos da; Silva, Marcos Vinícius da; Silva, Jhon Lennon Bezerra da; Marques, Rodrigo Ferraz Jardim; Alba, Elisiane; Nascimento, Antônio Henrique Cardoso do; Silva, Araci Farias; Silva, Elania Freire da; Cézar Bezerra, Alan (MDPI, 2024)
Caatinga is a typical Brazilian biome facing severe threats despite its ecological and socio-economic importance. Conservation strategies are essential in protecting ecosystems and ensuring natural resource sustainability. Mata da Pimenteira State Park (PEMP), launched in 2012, is an example of such a strategy. The current study aims to use orbital remote sensing techniques to assess human impacts on changes in land use and land cover (LULC) after the establishment of PEMP in the semi-arid region known as Caatinga, in Pernambuco State. The effects of this unit on vegetation preservation were specifically analyzed based on using data from the MapBiomas Brasil project to assess trends in LULC, both in and around PEMP, from 2002 to 2020. Man–Kendall and Pettitt statistical tests were applied to identify significant changes, such as converting forest areas into pastures and agricultural plantations. Trends of the loss and gain of LULC were observed over the years, such as forest areas’ conversion into pasture and vice versa, mainly before and after PEMP implementation. These findings highlight the importance of developing conservation measures and planning to help protecting the Caatinga, which is a vital biome in Brazil.
Keywords: Caatinga biome; conservation units; environmental degradation; land use trends; orbital remote sensing; semi-arid northeastern Brazil